Analisis Strategi Pengembangan Bisnis Pengolahan Minyak Eucalyptus - Juwanda Dewi Lestari; David Oscar Simatupang (Universitas Musamus, Merauke, Papua, 2018)
The strategies used in development of Eucalyptus oil refinery business are increasing the plantingnumber of Eucalyptus tree in Yanggandur Village, extending the marketing inside and outside area bypromoting the quality of production and also increasing the number of production activity inYanggandur Vaillage, providing the business modal aid and increasing number of refinery tools andsocialization of the importance of business management and packing technique of Eucalyptus oil,increasing the production by environmental preservation cooperated with the local society ofYanggandur Village in order to help their economic, and organizing the group of Eucalyptus oilrefinery business which divided into field of production, financial, marketing in order to control thebusiness.